Primary open angle glaucoma management in a tertiary eye care center in Saudi Arabia: a best practice implementation pilot project. Issue 2 (5th June 2021) - Alshowaeir, Daniah; Almasoud, Nouf; Aldossari, Sheikhah; Alsirhy, Ehab Y.; Osman, Essam; Turjoman, Abdulsalam; Amer, Yasser; Munn, Zachary; McArthur, Alexa
ABSTRACT: Aim: Primary open angle glaucoma (POAG) is a leading cause of permanent visual loss affecting significant numbers in Saudi Arabia. There is no cure for glaucoma but there is mounting evidence to guide ophthalmologists in diagnosing and managing this disease. The aim of this pilot project was to assess the compliance with evidence-based criteria and to implement an adapted clinical practice guideline (CPG) for the management of patients with POAG at a tertiary eye care center in Riyadh, Saudi Arabia that will lead to improving quality, consistency and optimizing patients' care. Methods: The project consisted of three phases using audit and feedback strategy. It has utilized the Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research into Practice audit and feedback tool. Eleven evidence-based audit criteria were developed. A baseline audit was then conducted. Barriers behind areas of noncompliance were identified and a number of strategies were implemented to overcome them. A follow-up postimplementation audit was then conducted. Results: Twenty electronic medical files were randomly selected for baseline audit. The results of the audit have identified a number of possible areas to improve in the diagnosis and management of POAG in compliance with the adapted CPG with compliance rate as low as 20% (4/20) in some criteria. Multifaceted interventions were implemented targeting mainly attitude and lack of knowledge and time and resource barriers. Significant improvement occurred in most criteria audited postimplementation. Conclusion: The project demonstrates that audit and feedback is a feasible and effective tool to change glaucoma practice in a teaching hospital in Saudi Arabia. The success was due to multifaceted interventions including clear communication to promote awareness, an easily accessible CPG, and regular reminders to improve knowledge and change behavior. We propose our pilot implementation to be generalized to promote implementing evidence-based ophthalmology.